Tax Policy : Designing and Drafting a Domestic Law to Implement a Tax Treaty - Nakayama, Kiyoshi (Washington, D.C. : International Monetary Fund, 2011)
Technical Notes and Manuals are produced by IMF departments to expand the dissemination of their technical assistance advice. These papers present general advice and guidance, drawn in part from unpublished technical assistance reports, to a broader audience. This new series was launched in August 2009.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country; Domestic Law; Tax; TNM; Treaty; United States